ON current enhancement and variability suppression in tunnel FETs by the isoelectronic trap impurity of beryllium. (29th January 2021) - Ban, Yoshisuke; Kato, Kimihiko; Iizuka, Shota; Moriyama, Satoshi; Ishibashi, Koji; Ono, Keiji; Mori, Takahiro
Abstract: We have experimentally demonstrated ON current enhancement and variability suppression of Si tunnel FETs (TFETs) by introducing an isoelectronic trap (IET) beryllium into the channel. In the previous studies, it was showed that the introduction of the Al-N IET impurity enables those requirements for Si-TFETs. In this study, we focused on Be as a new IET impurity and introduced the new IET into Si-TFETs. We found the optimum conditions for the formation of the Be-IET state in Si and demonstrated process integration of the Be-IET formation and TFET fabrication. The Be-introduced TFET exhibits five times enhancement of ON current; this enhancement ratio is larger than the case of the Al-N IET. Furthermore, significant suppression of the variability is achieved by Be-IET as well as the previous case of the Al-N IET. This better ON current improvement by Be-IET results from the energy level of Be deeper than that of Al-N IET, which plays a better role in enhancing the performance of Si-TFETs.